The Potential Role of Mitochondrial Acetaldehyde Dehydrogenase 2 in Urological Cancers From the Perspective of Ferroptosis and Cellular Senescence - Zhu, Weizhen; Feng, Dechao; Shi, Xu; Wei, Qiang; Yang, Lu (Frontiers in Cell and Developmental Biology, 2022)
Overproduction of reactive oxygen species (ROS) and superlative lipid peroxidation promote tumorigenesis, and mitochondrial aldehyde dehydrogenase 2 (ALDH2) is associated with the detoxification of ROS-mediated lipid peroxidation-generated reactive aldehydes such as 4-hydroxy-2-nonenal (4-HNE), malondialdehyde, and acrolein due to tobacco smoking. ALDH2 has been demonstrated to be highly associated with the prognosis and chemoradiotherapy sensitivity of many types of cancer, including leukemia, lung cancer, head and neck cancer, esophageal cancer, hepatocellular cancer, pancreatic cancer, and ovarian cancer. In this study, we explored the possible relationship between ALDH2 and urological cancers from the aspects of ferroptosis, epigenetic alterations, proteostasis, mitochondrial dysfunction, and cellular senescence.